Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Cerita Materi Kubus Dan Balok Kelas VIII MTs Negeri Sukoharjo Tahun 2016/2017 - Nasrudin, Reqy Thoat, Dra. Sri Sutarni, M.Pd (2017)
This study aims to determine the types of error and causes of students to make mistakes in solving the cube and block shape of the story based on stages analysis method Kastolan. This research was descriptive qualitative research. These research subjects were 38 students from class VIII B MTs Negeri Sukoharjo. Technique of data in this research is to using the test method, interviews, and documentation. Data validation was done by triangulation technique by comparing the test data, interviews, and documentation. Data analysis technique was done by means of data reduction, data presentation, and verification of data and making conclusions. Based on the analysis we concluded that (1) 35,26% of students experienced a conceptual error with the level qualificaton low error, (2) 56,32% of students experienced procedural error with a medium qualification level error, and (3) 47,89% students experienced technical error with a medium qualification levels. The causes of the error is that students do not understand the intent of the problem, students are wrong in choosing the formula, students can not apply the formula, not appropriate steps in solving the problem, students do not practice in doing the problem, meticulous in answering questions, and in a hurry so as not to check back the results of this work.